2014
DOI: 10.1007/s10120-014-0417-4
|View full text |Cite
|
Sign up to set email alerts
|

Preferential HER2 expression in liver metastases and EGFR expression in peritoneal metastases in patients with advanced gastric cancer

Abstract: Background Despite recent clinical trials, the sensitivity and resistance of metastatic gastric cancer to anti-HER2 and anti-EGFR therapy are still unclear. Materials and methods To clarify the HER2 and EGFR expression status in the metastatic sites, we immunohistochemically compared HER2 and EGFR expression between primary and metastatic tumors from 52 gastric cancer patients with liver metastases and 85 patients with peritoneal metastases. Results The HER2 positivity rate of primary and metastatic tumors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Positive conversion was more frequent than negative one (10.8 % vs. 5,4 %) [19]. These results were also confirmed by other recent reports conducted on Asiatic patient cohorts [20][21][22].…”
Section: Discussionsupporting
confidence: 94%
“…Positive conversion was more frequent than negative one (10.8 % vs. 5,4 %) [19]. These results were also confirmed by other recent reports conducted on Asiatic patient cohorts [20][21][22].…”
Section: Discussionsupporting
confidence: 94%
“…In contrast, other studies that queried discordance of ERBB2 within distinct regions of the PT found discrepancies in only 12% of cases (27,28), or that patients with metastatic GEA with negative ERBB2 testing from a biopsy of the PT showed ERBB2 positivity in the metastatic disease in only 5.7% of cases (29). In addition, other studies have shown 87.5% to 98.5% concordance of ERBB2 between PT and paired metastatic sites (30,31). Based upon these existing data, new 2016 guidelines for assessment of ERBB2 status in GEA recommend that testing be performed on a single site, either the PT or metastases, stating that the totality of literature does not suggest common heterogeneity of ERBB2 between sites (32).…”
Section: Introductionmentioning
confidence: 91%
“…Another situation that seems to increase the incidence of HER2+ is the proximal third tumors [22, 23], but such a site accounts for only one-third of the sample of our patients. Moreover, some studies [24] suggest an association between greater expression of HER2 and the presence of hepatic metastases. Nevertheless, no patients in this situation were included in our study, as we understand that both the metastatic disease and the residual tumor following palliative resections are situations which clearly compromise the survival time and interfere with the analysis of the results, as one of the objectives of this study was to verify the incidence of HER2 expression in gastric cancer and its possible relationship with survival.…”
Section: Discussionmentioning
confidence: 99%